Por uma abordagem cognitiva da pressuposição : modelos cognitivos idealizados e propagandas - Feriguetti, Karen Muniz (2008)
This work presents two approaches of presupposition: The formal and the cognitivist ones. Initially, a paper was done taking the authors of both segments, focusing and underlining names such as Frege (1982), Russel (1905), Strawson (1950) and Austin (1962), in the philosophy, Ducrot (1977, 1981, 1987), in the linguistic, concerning to formalism; also Lakoff and Fauconier, concerning to the experiential realism. Connected to this proposal we have the discussion of the semantic or pragmatic character of the presupposition, always present in the formal linguistic thought. In relation to the formalism, postulates that guide the studies of the langue/language in its immanence, in its more restrict sense, will be presented. In turn, concerning to the cognitivism of existential realistic basis, which defend a procedure that takes into account the language cognitive process in its use, we took the hypothesis brought by Lakoff and Fauconnier that the presupposition triggers cognitive models thoughts and introduces mental spaces, as also proposes Marmaridou. In a second moment, we applied the theoretical postulates to the propaganda of the 58 SBPC, of the scientific magazine entitled “Science Today”, in a representative example of a definite description, showing, through a contrastive analysis, the theoretical possibilities of the approaches presented here. We provided not only the hypothesis defended by Marmaridou but also the possibility of a third via to the vicissitudes of a formalist study, the unified treatment, according to Fauconnier, facing the formalism that quarrels with the semantic and pragmatic character of the presupposition.